Hypoxic conditions interrupt flood‐response movements of three lowland river fish species: Implications for flow restoration in modified landscapes. Issue 3 (14th February 2020) - Thiem, Jason D.; Wooden, Ian J.; Baumgartner, Lee J.; Butler, Gavin L.; Taylor, Matthew D.; Watts, Robyn J.
Abstract: Movement and migration of freshwater fish for the purpose of feeding, dispersal, and spawning are essential life history components often linked to river flows. Understanding movement responses to abiotic stimuli such as river flows is crucial to inform effective management, especially considering that river regulation is contributing to global population declines. We examined the flow‐related movements of three species of lowland river fish endemic to eastern Australia (golden perch Macquaria ambigua, Murray cod Maccullochella peelii, and silver perch Bidyanus bidyanus ) over an 18‐month period in a large anabranch system of the Murray River, south‐eastern Australia. The telemetry study encompassed periods of extreme low river discharge, moderate discharge rates within the normal regulated operating range for this system, and a large overbank flood event that created hypoxic blackwater conditions and led to significant fish kill events. Movement of all three species was strongly affected by discharge rates, and although the direction and magnitude of responses varied by species, river discharge in general had a significant positive effect on the scale of movement. All species initiated large‐scale directional movements in response to flooding, and some emigration occurred; however, hypoxia‐induced mortality ultimately killed a large proportion of the tagged fish. The results of the current study highlight the significant challenges of managing flow restoration in highly modified landscapes that are prone to hypoxic conditions. We reiterate the value of connectivity, especially where it enables fish to access suitable refuges during periods of poor water quality and subsequently recolonize when conditions improve.